Vinorelbine versus paclitaxel for patients with advanced non-small cell lung cancer (NSCLC) and a performance status of 2 - Kosmidis, P.A.; Syrigos, K.; Kalofonos, H.P.; Dimopoulos, M.-A.; Skarlos, D.; N. Pavlidis; Boukovinas, I.; Bafaloukos, D.; Pectasides, D.; Bacoyiannis, C.; Fountzilas, G. (Anticancer Research, 2012)
Aim: The purpose of this study was to compare two single agents paclitaxel (intravenous) versus vinorelbine (oral) in non-small cell lung cancer (NSCLC) patients with performance status (PS):2. Patients and Methods: The patients were randomized to receive either oral vinorelbine 60 mg/m 2 on days I, 8, 15 every 4 weeks for 4 cycles (group A) or paclitaxel 90 mg/m 2 intravenously for 1 h on days 1, 8, 15 every 4 weeks for a total of 4 cycles (group B). Results: Among the 74 eligible patients (36 in arm A and 38 in arm B) in arm A, two (6%) had a partial response (95% Cl, 0.7-18.7) and 5 (14%) had stable disease (95% CI, 4.7-29.5). In arm B, five (13%) had a partial response (95% CI, 4.4-28.1) and 7 (18%) had stable disease (95% CI, 7.7-34.3). No significant difference was found in terms of clinical benefit between the two groups after two cycles of treatment except for appetite in favour of paclitaxel (p=0.01). Median survival was 3.1 months (95% CI, 2.2-4.0) for arm A and 5.1 months (95% CI, 2.7-7.6) for arm B (p=0.95). Toxicity was mild and only alopecia was more profound in the patients of arm B (p=0.008). Conclusion: No significant difference was found in clinical benefit between PS:2 NSCLC patients treated with either vinorelbine or paclitaxel.
Keywords: Chemotherapy; Clinical benefit; Non-small cell lung cancer; Paclitaxel; Performance status of 2; Vinorelbine